Correlation between chronic inflammation of rheumatoid arthritis and coronary lesions: “About a monocentric series of 202 cases” - Zaoui, Nassime; Boukabous, Amina; Irid, Nabil; Bachir, Nadhir; Terki, Ali (Journal of Cardiology and Cardiovascular Medicine, 2022)
Introduction: Cardiovascular diseases are the leading cause of death in the world, headed by coronary artery disease, which is secondary to atherosclerosis. The latter recognizes classic risk factors such as diabetes, high blood pressure, tobacco, and dyslipidemia and other less classic factors such as chronic inflammation of rheumatoid arthritis. Many studies have highlighted the correlation between this chronic inflammation and clinical coronary disease but very few have focused on the anatomical correlation. Objective: To describe the correlation between the chronic biological inflammation of rheumatoid arthritis and anatomical coronary lesions on angiography. Method: This observational, retrospective, single-center study, including over 10 years, of patients with rheumatoid arthritis, confirmed the EULAR 2010 criteria and presented with coronary artery disease requiring coronary angiography. Patients with missing data or in whom coronary angiography was not done were excluded (n = 14). We divided then the patients according to the existence or not of chronic inflammation to study the impact of the latter on the existence (Stenosis < 50% vs. stenosis ≥ 50%), the extent (single vs. multivessel disease), and the severity of the coronary lesions (syntax score < 32 vs. ≥ 32). Results: 202 patients (49♂/153♀) aged between 30-75 years with a history of rheumatoid arthritis have had a coronary event requiring coronary angiography, were included; The mean ejection fraction at baseline was 57.3% +/- 5.8 (37 vs. -65%). 75% of them were ≥ 65 years old. 55% were diabetics, 61% with hypertension, 38% with dyslipidemia, and 19% were smokers. Chronic inflammation was diagnosed in 70% of them on non-specific parameters (ESR, CRP, fibrinogen, anemia, and rheumatoid factor). All patients had coronary angiography, which made it possible to identify the coronary lesions according to their existence (Stenosis < 50%: 51 patients vs. stenosis ≥ 50%: 151 patients), the extent (single: 86 patients vs. multivessel disease: 116 patients) and the severity of the coronary lesions (syntax score < 32: 142 patients vs. ≥ 32: 60 patients). Chronic inflammation of rheumatoid arthritis was correlated in bivariate and multivariate analysis (after excluding the impact of other risk factors) with the existence and extent of coronary lesions (p < 0.05) but not with their severity (p > 0.05). Discussion: The two limitations of this work are the monocentric nature of the study and the absence of specific inflammatory parameters such as anti-CCP antibodies. Strengths are anatomical correlations and multivariate analysis. Chronic inflammation apart from any influence of the various risk factors predisposes to the existence and extent of coronary lesions (p < 0.05). The severity of coronary lesions assessed by Syntax Score was not correlated with chronic inflammation, although other studies suggest that this inflammation is the cause of complex lesions. Interpretation: Rheumatoid arthritis is associated with an increase in cardiac morbidity and mortality. Atheromatous lesions are more frequent in those patients than the existence of classic cardiovascular risk factors would suggest. Several explanations could account for this risk: the inflammatory syndrome and its impact on the cardiovascular risk factors and the vessel and the deleterious effect of the treatments. This requires stricter screening and management of risk factors in rheumatoid arthritis.